Melaleuca alternifolia essential oil abrogates hepatic oxidative damage in silver catfish (Rhamdia quelen) fed with an aflatoxin-contaminated diet - de Freitas Souza C. (2019)
© 2019 Elsevier Inc.Mycotoxins are secondary metabolites produced by varieties of fungi that contaminate food and feed resources and are capable of inducing a wide range of toxicity. This problem is extensively aggravated due to the increasing replacement of fish meal by plant-derived proteins. Among the mycotoxins, aflatoxins have received a great deal of attention owing to their great prevalence in plant feedstuffs and to the detrimental effects on animals. The objective of this study was to evaluate whether dietary supplementation with tea tree (Melaleuca alternifolia) oil (TTO) would avoid or minimize the negative impacts on silver catfish (Rhamdia quelen) fed with aflatoxins-contaminated diets. Four treatments were tested: control (fish fed with a control diet); AFB (fish fed with a mycotoxin-contaminated diet – 1893 μg kg−1 of AFB1 and 52.2 μg kg−1 AFB2); TTO (fish fed with a control diet + 1 mL kg−1 of TTO), and TTO + AFB (fish fed with a mycotoxin contaminated diet - 2324 μg kg−1 of AFB1 and 43.5 μg kg−1 AFB2 + 1 mL kg−1 of TTO). Diets were tested in three replications and analyzed at days 5 and 10 of dietary intake. Significantly reduced antioxidant enzymes (SOD, GPx, and GST) and increased lipid peroxidation (LOOH) and protein carbonyl (PC) content in plasma and liver, with 16.6% mortality occurrence, were observed in the group fed aflatoxin-contaminated diet. Furthermore, aflatoxins also significantly increased plasmatic and hepatic ROS levels and decreased hepatic antioxidant capacity against peroxyl radical (ACAP) levels. Plasma cortisol levels were not altered by aflatoxicosis, but the intoxication induced hepatose. Notwithstanding, addition of TTO to the groups receiving aflatoxins showed a protective effect, avoiding the increase of ROS, LOOH, and PC levels in plasma and liver. Moreover, TTO treatment ameliorated the aflatoxin-associated liver damage. Thus, TTO supplementation at concentration of 1 mL kg−1 in feed may be used in fish to increase antioxidant status and reduce the negative effects caused by aflatoxins toxicity.